Comparation of Limit Equilibrium Method (LEM) 2D on Safety Factor and Embankment Reinforcement - Hapsari, Aisiyah Pramaisela; Lastiasih, Yudhi (Journal of Infrastructure & Facility Asset Management, 2024)
The analysis of slope stability is crucial during embankment planning to ensure safety and prevent landslides. A stable slope ensures the safety of surrounding infrastructure, minimizing the risk of damage. Therefore, with slope stability analysis can manage and maintain infrastructure assets. The primary method used to evaluate slope stability is the Limit Equilibrium Method, frequently employed in a 2D framework using various applications such as Plaxis LE and Geostudio. Using diverse applications for analysis can yield varying safety factors, influencing the required reinforcement. Hence, this study analyzed safety factors and the necessary geotextile reinforcement for embankments on soft soil featuring distinct heights, slopes, and widths in 2D. The analysis was performed using the Plaxis LE application, and the results were subsequently compared with those obtained from the Geostudio application. This research shows that the results of the embankment safety factors with the Plaxis LE application are different from those of the embankment safety factors with Geostudio, resulting in different embankment geotextile reinforcement namely the need for Plaxis LE geotextile reinforcement = 0.7 Geostudio geotextile reinforcement.